STUDI KOMPARATIF KEARIFAN LOKAL TERHADAP PERTUMBUHAN EKONOMI DI JAWA TIMUR - Ariz Aprilia; Nofita Wulansari (UNEJ e-Proceeding)
East Java is one of the provinces in Indonesia that has become the object of numerous studies. The potentia development l of the region based on local wisdom become a major destination for local government in East Java today. Various districts in East Java have abundant wealth of local knowledge and become the biggest factor in the acceleration of economic growth. In this paper we sought to identify the factors that influence local knowledge to economic growth in East Java. Factors that we use include human factors and natural factors. By using VAR (Vector Autoregressive), this paper produced findings that natural factors becomes the dominant factor that influincing the economic growth in East Java.